Effects of regression parameters on eos in PVT properties [electronic resource] - 369028 Muhammad Hafizzudin Baharudin (2006)
Project Paper (Sarjana Muda Kejuruteraan (Petroleum)) - Universiti Teknologi Malaysia, 2006